Serotonin transporter (5-HTT) promoter genotype may influence the prolactin response to clomipramine. - Whale, R; Quested, D; Laver, D; Harrison, P; Cowen, P (2000)
RATIONALE: A 44-base-pair insertion/deletion polymorphism in the promoter region of the human serotonin (5-HT) transporter (5-HTT) gene gives rise to a bi-allelic polymorphism designated long (l) and short (s). The s variant is associated with a lower expression of 5-HTT sites and a reduced efficiency of 5-HT reuptake. OBJECTIVE: The aim of the present study was to determine whether the increase in brain 5-HT function produced by acute 5-HT reuptake blockade is influenced by the 5-HTT promoter l/s polymorphism. METHODS: We measured the increase in plasma prolactin that follows acute administration of the tricyclic antidepressant clomipramine as an index of 5-HT neurotransmission in 14 healthy female subjects (7 with ss genotype and 7 with ll genotype) using a placebo-controlled crossover design. RESULTS: Clomipramine-induced prolactin release was significantly greater in subjects with the ll genotype. CONCLUSION: Our findings suggest that acute 5-HT reuptake blockade produces a greater increase in 5-HT neurotransmission in subjects with the ll genotype than in those with an ss genotype. These results are consistent with clinical data indicating that subjects with an ss genotype may have a poorer therapeutic response to selective serotonin reuptake inhibitor (SSRI) monotherapy.